Temporal and Spatial Evolution Characteristics Analysis of Beijing Land Subsidence Based on InSAR. Issue 1 (February 2021) - Muhetaer, Nijiati; Yu, Jie; Wang, Yanbing; Yue, Jiabao
Abstract: Land subsidence is one of the main geological disasters in the Beijing Plain. Accurate and quantitative monitoring of the evolution of land subsidence will help scientifically guide the prevention and control of land subsidence. We use PS-InSAR technology and TerraSAR 3m resolution images as our data source to study the temporal and spatial evolution characteristics of Beijing's land subsidence from 2012 to 2015. The research indicates that, from a spatial perspective, the land subsidence presents a funnel shape, the central area of the settlement funnel is maintained at 112.5km², and the total land subsidence area remains basically unchanged. From the temporal point of view, the central area of the ground subsidence funnel subsides at a rate of 110mm/y, the ground subsidence rate in other areas decreases as it far away from the settlement center.